Reached - Condie, Allyson Braithwaite (New York, New York : Dutton Books, an imprint of Penguin Group (USA) Inc., 2013)
"In search of a better life, Cassia joins a widespread rebellion against Society, where she is tasked with finding a cure to the threat of survival and must choose between Xander and Ky"--
Sequel to: Crossed.
Keywords: Government, Resistance to -- Fiction; Fantasy